VHDL Modeling Of Fetal QRS Complex Detection Algorithm - Tan, Hung Khoon (2004)
Fetal Heart Rate (FHR) monitoring using electrocardiogram (ECG) is important to detect the condition of the fetus during pregnancy. An algorithm has been adopted and improved to extract the maternal and fetal QRS interval from the raw AECG data. The algorithm is based on cross-correlation, adaptive thresholding and maternal template subtraction.